Long-term outcomes in patients with endometrial cancer after sentinel lymph node biopsy versus lymphadenectomy alone: a meta-analysis - Zhang, Sai; Zheng, Juan; Zhu, Dandan (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to assess the prognosis of endometrial cancer (EC) patients after sentinel lymph node biopsy (SLNB) or lymph node dissection (LND) alone.MethodsEMBASE, PUBMED, COCHRANE, and WEB of SCIENCE were thoroughly searched for relevant articles until October 2024. The outcomes of interest encompassed overall survival (OS), progression-free survival (PFS), and disease-specific survival (DSS). Data analysis was made in STATA 18.0. The Newcastle-Ottawa Scale tool was leveraged to appraise study quality.Results13 studies were included, involving 36621 EC patients. No difference was revealed in OS between SLNB and LND (HR=1.04, 95%CI: 0.80–1.33; P=0.789). In subgroup analyses, the SLNB group from survival curves had worse OS (HR=1.63, 95%CI: 1.04-2.56; P=0.035); the SLNB group with intermediate- to high-risk EC had better OS (HR=0.20, 95%CI: 0.08-0.49; P<0.001). No difference was revealed in PFS between SLNB and LND (HR=0.99, 95%CI: 0.76–1.28; P=0.927). SLNB had better PFS in Asia (HR=0.44, 95% CI: 0.20-0.98, P=0.046) and stage I-III EC (HR=0.46, 95% CI: 0.24-0.89; P=0.021). No statistical difference was found in DSS (HR=3.18, 95%CI: 0.91-11.07; P=0.069).ConclusionSLNB is an effective alternative to conventional LND in either low- or intermediate-high-risk EC patients. However, due to the retrospective nature of most included studies and the limited data on high-risk patients, further prospective randomized controlled trials are warranted to validate these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD42024489323.